Prospect for increasing grain legume crop production in East Africa - Loon, Marloes P. van; Deng, N.; Grassini, P.; Edreira, J.I.R.; Woldemeskel, Endalkachew; Baijukya, Frederick P.; Marrou, H.; Ittersum, Martin K. van (Elsevier, 2018)
Agricultural production in East Africa (E-Afr) has to increase drastically to meet future food demand. Yield gap assessment provides important information on the degree to which production can be increased on existing cropland. Most research on yield gap analysis has focussed on cereal crops, while legumes have received less attention despite of their relatively large area, and their importance as source of protein in smallholder farming systems in E-Afr. The objectives of this study were to (i) estimate water-limited yield potential (Yw) and yield gaps (Yg) for major grain legume crops in E-Afr, and (ii) estimate how narrowing the current legume Yg can contribute to food self-sufficiency by the year 2050. We focussed on Ethiopia, Kenya, and Tanzania, and five legumes crops including chickpea, common bean, cowpea, groundnut, and pigeonpea. A bottom-up approach which entails that local weather, soil and agronomic data was used as input for crop modelling (SSM-legumes) in a spatial framework, to estimate Yw, actual on-farm yield (Ya), and Yg from local to regional scale. Future legume self-sufficiency was assessed for 2050 demand assuming different Yg closure scenarios. On average, Ya was 25% of Yw across all legume-county combinations, being 15% for Kenya, 23% for Tanzania and 41% for Ethiopia. On average, common bean had the largest Yg of 2.6 Mg ha−1and chickpea the smallest (1.4 Mg ha−1). Closure of the exploitable Yg (i.e., 80% of Yw) can help to meet future legume demand in both Kenya and Tanzania, while it seems not to be sufficient in Ethiopia.